2021
DOI: 10.1177/1535759721999670
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Super-Refractory Status Epilepticus: A Review

Abstract: Purpose: Super-refractory status epilepticus (SRSE) presents management challenges due to the absence of randomized controlled trials and a plethora of potential medical therapies. The literature on treatment options for SRSE reports variable success and quality of evidence. This review is a sequel to the 2020 American Epilepsy Society (AES) comprehensive review of the treatment of convulsive refractory status epilepticus (RSE). Methods: We sought to determine the effectiveness of treatment options for SRSE. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 91 publications
0
17
1
2
Order By: Relevance
“…Super-refractory SE is defined as seizure activity >24 h despite treatment with anesthetic agents. This includes cases in which seizures recur with an attempted withdrawal of the anesthetics ( 76 ). Effective treatment of SE is critical as morbidity and mortality increase dramatically the longer convulsive SE persists.…”
Section: Epilepsy In Dogsmentioning
confidence: 99%
“…Super-refractory SE is defined as seizure activity >24 h despite treatment with anesthetic agents. This includes cases in which seizures recur with an attempted withdrawal of the anesthetics ( 76 ). Effective treatment of SE is critical as morbidity and mortality increase dramatically the longer convulsive SE persists.…”
Section: Epilepsy In Dogsmentioning
confidence: 99%
“…29,30 The clinical evidence is good for the earlier treatment stages, but refractory status epilepticus and super-refractory status epilepticus can still be considered an "evidence-free area." 31 This article does not follow the traditional scholarly approach but instead reviews status epilepticus as a process, spanning from the initial onset of symptoms to the application of continuous EEG in the neurologic intensive care unit (FIGURE 12-2). After some introductory information on definitions, classifications, epidemiology, and treatment principles, the article follows a patient's pathway through the treatment stages and focuses on the practicalities, supported by scientific evidence wherever possible.…”
Section: Minutes 30 Minutesmentioning
confidence: 99%
“…The clinical evidence is good for the earlier treatment stages, but refractory status epilepticus and super-refractory status epilepticus can still be considered an “evidence-free area.” 31 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]8] Further, when SE continues despite general anesthetic treatment for RSE over 24 h, it is called "SRSE. " [2,3,6,9,10,12,15] It has been reported that 24-48% of SE progresses to RSE and 15%-22% of RSE progresses to SRSE. [2,15] SRSE is recognized as a neurological emergency disease that is difficult to treat and has a poor prognosis, with death occurring in 35% of cases and 13% suffering from serious neurological sequelae.…”
Section: Introductionmentioning
confidence: 99%